2014
DOI: 10.1177/0886260514534526
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence in the Relationships of Men With Disabilities in the United States

Abstract: Despite the growing literature on intimate partner violence (IPV) victimization against people with disabilities, few studies have examined IPV against men with disabilities. This study uses population-based data to examine the prevalence of past-year and lifetime IPV against men with disabilities in the United States in comparison with men without disabilities and women with and without disabilities, compare the demographic characteristics of men with disabilities who reported IPV to those of other men, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…Previous studies established the heightened rates of IPV among men with disabilities (Cohen et al, 2006;Mitra et al, 2011;Mitra & Mouradian, 2014;Olofsson et al, Percentages represent the percentage of valid responses. b Some clients reported more than one disability type; therefore, percentage for this category adds up to greater than 100%, and n is greater than 70.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies established the heightened rates of IPV among men with disabilities (Cohen et al, 2006;Mitra et al, 2011;Mitra & Mouradian, 2014;Olofsson et al, Percentages represent the percentage of valid responses. b Some clients reported more than one disability type; therefore, percentage for this category adds up to greater than 100%, and n is greater than 70.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mitra and colleagues 11 found 2.6% of men with disabilities reported sexual abuse by an intimate partner compared with 1.1% of nondisabled men. Powers et al 7 found 9% reported sexual abuse by their personal care assistants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining the relationship between the perpetrator of sexual violence and men with disabilities have focused on sexual abuse by intimate partners 6,11 and personal care assistants. 7 Mitra and colleagues 11 found 2.6% of men with disabilities reported sexual abuse by an intimate partner compared with 1.1% of nondisabled men.…”
Section: Introductionmentioning
confidence: 99%
“…Since the publication of a meta‐analysis showing that adults with disabilities had a 1.5‐fold increase in the odds of interpersonal violence, there have been analyses of disability and violence of population‐based surveys in other high‐income countries. Prevalence estimates from the US show that 19% of men and 36% of women reported intimate partner violence in their lifetime compared to 13% of men and 22% of women without disabilities 10 . A US longitudinal study also found higher levels of intimate partner violence among those with disabilities compared to their non‐disabled counterparts, with an increased odds of 1.6 for those with both physical and mental health impairments 11 .…”
mentioning
confidence: 99%
“…while men with disabilities have a higher risk of physical and non‐domestic violence 12 . There is also evidence to suggest that men with disabilities are more likely to experience intimate partner violence than men without disabilities 10 …”
mentioning
confidence: 99%